Unexpectedly low levels of dental morphological asymmetry suggesting developmental resilience amongst living Jordanians: A cone beam computed tomography study - Sabrah, Ala’a H; Alzer, Heba; Al-Shayyab, Mohammad H; Alsoleihat, Firas; Alhadidi, Abeer (Homo, 2020)
The objective was to determine the degree of fluctuating asymmetry in the expression of 13 dental morphological traits among adult Jordanians. Cone beam computed tomography images for the dentitions of 150 adult Jordanians (67 males, 83 females; age range = 18–58, mean ages 28.2, SD = 10.0 years) were studied in 2017. The traits were classified using the Arizona State University dental anthropology system, and dichotomized according to the most widely accepted criteria to define trait presence. Asymmetry was assessed using three different methods: percentage of discordance including bilateral absence cases (PDIBAC), percentage of discordance excluding bilateral absence cases (PDEBAC), and inter-side correlation (ISC) using Kendall’s tau coefficient. Fisher’s exact test was used to assess sexual dimorphism in the degree of asymmetry. The mean PDIBAC and the mean ISC for all the traits considered are 4.1% and 0.837, respectively. For traits observed on key teeth (mesial members of teeth districts) the mean PDIBAC and the mean ISC are 3.0% and 0.860, respectively; and for those observed on variable teeth (distal members of teeth districts) the mean PDIBAC and the mean ISC are 6.5% and 0.783, respectively. No statistically significant difference was found in the degree of asymmetry between sexes. The overall low degree of asymmetry found in the present sample (4.1%) compared to the world range of 5-15% may indicate great ability of its individuals to buffer the adverse effects of environmental stresses affecting the living Jordanians during early tooth development.